Naked Exclusion - Rasmusen, Eric B.; Ramseyer, J. Mark; Wiley, John S. (American Economic Review, 1991)
Ordinarily, a monopoly cannot increase its profits by asking customers to sign agreements not to deal with potential competitors. If, however, there are 100 customers and the minimum efficient scale requires serving 15, the monopoly need only lock up 86 customers to forestall entry. If each customer believes that the others will sign, each also believes that no rival seller will enter. Hence, an individual customer loses nothing by signing the exclusionary agreement and will indeed sign. Thus, naked exclusion can be profitable.